Communication network analysis - Gideon de Wet (Communicare)
This study firstly aimed to Illustrate the innovative value of network analysis for the development communication researcher. A case study with the emphasis on an intact system of farmers in the Border-Kelarsalis presented. The study was conducted in Komkhulu with. 46 local farmers taking part in the research. Network analyses were done on a "Who to whom?" matrix basis in order to determine and to illustrate the dynamic Interrelatedness amongst Intact system members and its potential research value for communication and development researchers. Network analysis research In this study concentrated on three levels, namely, the system, clique and Individal levels of analysis. A conceptual picture of dynamic network analysis aspects was revealed. The conceptual quality of network analysis is further enriched by the use and application of the open-systems approach orientation and the communication convergence orientation. The emphasis is not on the effects of communication, but rather on what is taking place among system members. Lastly, social scientists and development communication researchers in particular are encouraged to use network analysis in con junction with or in support of other methodological orientations in community development research. granted lay the Panther (dated 2010